EFEKTIFITAS EKSTRAK ETANOL DAUN RUMPUT MALAYSIA (Chromolaena odorata L) PADA LUKA DIABETES MENCIT JANTAN (Mus muscullus) - Setya Enti Rikomah; Fiske Rani Firdita (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Diabetic wounds are a form of diabetic complications that results in wounds experiencing deeper tissue damage and a longer healing process due to the condition of hyperglycemia. One of the plants known to the community as a wound medicine is the Malaysian grass plant (Chromolaena odorata L). The purpose of this study was to determine whether the ethanol extract of Malaysian grass leaves can accelerate the wound healing process in diabetes mice.The research process using the induction of alloxan monohydrate and the wound observed in this study was a cut. Diabetes mice were injured along 1.5 cm on the back of the scalpel and then divided into 5 treatment groups namely not treated (KN), ointment Betadine® (KP), ethanol extract of Malaysian grass leaves at a dose of 5 mg (P1), 10 mg ( P2) and 15 mg (P3). Basting is done twice a day for 14 days.One Way Anova analysis results 0.033> 0.05 which shows that there are significant differences between each treatment group. In the study it was found that treatment group 3 with a dose of 15 mg better accelerated wound healing and followed by positive control and treatment group 1.